Presence and perceived learning in different higher education blended learning environments - Wan Ali, Wan Zah; Khodabandelou, Rouhollah; Jalil, Habibah; Mohd Daud, Shaffe (IGI Global, 2015)
Blended learning as “third generation” of distance learning has the potential to offer multimethod instruction through the blend, to leverage the strengths of current online and traditional instructions. Therefore, higher education institutions having recognized the fact that blended learning is beneficial, adopted this alternative approach as a new educational delivery method. The study determined the difference in perceived learning among three different blended learning environments in Malaysian higher education institutions. The data were collected from three public universities in Peninsular Malaysia and the respondents were undergraduate students from these universities. The result showed that the students’ presence in classroom meetings contributes to their learning. The results also indicate that high levels of perceived learning were reported by undergraduate student in the blended learning environment face-to-face meeting rather than online sessions.